Childhood in medieval Poland (1050-1300) : constructions and realities in a European context - Koval, Matthew B. (East Central and Eastern Europe in the Middle Ages, 450-1450 ;, 2021)
"This volume analyses the constructions and realities of childhood in Poland, c. 1050-1300 CE, by examining a range of texts and considering the ways in which children fit within textual frameworks and genres. These texts include two major chronicles, monastic sources, and hagiography related to five major saints. The textual sources are put into conversation with findings from archaeology. The author argues that certain common themes, such as assumed care for children, the need for education, and the puer senex trope do feature through most texts of any genre, and the book also explores how Poland was similar to and different from the situation in western Europe"--